The Role of Mamanda Traditional Theatre in Building the Character of the Youth Generation in South Kalimantan - Haswinda Harpriyanti; Yasyir Fahmi Mubaraq; Agustina Lestary (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The millennial era brings many new challenges in life, both in the development of technology and education and especially in the identity of the younger generation. The millennial era continues to demand the younger generation to be able to upgrade themselves to be more active, creative and innovative. This, without realizing it, can also have a negative impact, especially on the importance of character values ??that must be owned by the younger generation so as not to lose their identity as a nation based on Pancasila and cultured. This study aims to describe how Mamanda traditional theatre can play a role in building the character of the younger generation, especially young people in Banjarmasin, South Kalimantan and describe the community's response to Mamanda's performances. This research was conducted by observing Mamanda's performances in various activities. This study uses descriptive qualitative research methods because it will describe clearly and in detail the results of the study. The results of this study describe that the role of Mamanda traditional theatre in building character can be done by inserting character education values ??into the delivered stories, such as faith, politeness, and local cultural values ??of the Banjar people. In addition, the community's response to Mamanda's traditional theatre shows that Mamanda is considered to be able to provide many positive impacts for the Banjar community, and it is hoped that Mamanda can continue to exist during the rapid development of the current era.